ECCLESIAL VISION OF SAINT THOMAS CHRISTIANS IN THE LIGHT OF VARTHAMANAPPUSTHAKAM: A HISTORICO-THEOLOGICAL STUDY - Valiamangalam, Jose Thomas (Asian Horizons, 2015)
This study on Varthamanappusthakam (VP) brings out the knowledge of the ecclesial identity, autonomy and ecclesial heritage of the Thomas Christians. The importance of VP with regard to the Malabar Church is that it is an eyewitness’ account of the life of the said Church between 1778 and 1786. It is a praxis theology from the Indian soil. This is a research study on the VP from an ecclesiological point of view of the Thomas Christians but the accent is on Pazhayakuttukar (Old group) of the Malabar Church. The famous dictum Sentire cum Ecclesia was very much applicable in the lives of Malpan Joseph Cariattil and Cathanar Thomman Paremmakkal. This study helps to bring out the ecclesiological vision of the Thomas Christians from the internal evidences of VP, such as the ardent love for the Mother Church, their deep faith in God, the liturgical life, the spiritual heritage and the form of an indigenous administration. VP is used as the original source in the entire study.